PERANCANGAN APLIKASI BERBASIS WEB UNTUK PEMESANAN PRODUK EKSTERIOR DAN INTERIOR PADA BENGKEL LAS KRISNA - Arvelia Yoshianne Anggie; Jap Tji Beng; Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
One way to create information services for consumers is to create a website. At this time the website is easily accessible by the public, besides that the website also has many advantages, namely being able to provide information accurately, easily and quickly to be accessed which can help consumers to find out about a product that is needed. Welding workshop business is a business that is much needed by the community. Krisna welding workshop is a workshop engaged in the business of welding services and the manufacture of exterior and interior products that use iron as basic materials. To help make it easier to provide information to consumers and help process reports, a web-based application design is made for ordering iron-based exterior and interior products at a krisna welding workshop. The method that will be used to design this application is to use the waterfall method. Using the waterfall method so that the design made can be more structured because the waterfall method has stages that can make the flow of this design run more optimally. And of course the transaction can run smoothly, and the flow of the transaction process can be well structured.